(untitled) (New Jersey, 2005)
This book is a basic reference providing concise, accurate definitions of the key terms and concepts of organic chemistry. Not simply a listing of organic compounds, structures, and nomenclatures, the book is organized into topical chapters in which related terms and concepts appear in close proximity to one another, giving context to the information and helping to make fine distinctions more understandable. Areas covered include: bonding, symmetry, stereochemistry, types of organic compounds, reactions, mechansims, spectroscopy, and photochemistry.
Keywords: Chemistry, organic; Dictionary